Action research studies in the intensive care setting: A systematic review - Soh, K.; Davidson, P.; Leslie, Gavin; Rahman, A. (2011)
Objectives: To review published studies using action research in the intensive care unit (ICU) in order to provide an intervention framework to improve clinical outcomes. Design: Systematic review. Methods: Searches of the electronic databases: Cumulative Index of Nursing and Allied Health Literature (CINAHL); Scopus, Medline, Embase, PsycINFO, and the World Wide Web were undertaken using MeSH key words including: 'action research'; 'health care research', 'health services evaluation'; 'intensive care unit'. Reference lists of retrieved articles was also undertaken to identify further articles. All studies were reviewed by two authors using a critical appraisal tool. Results: The search strategy generated 195 articles. Only 21 studies projects were identified using action research in the ICU. The majority of studies were conducted in the United Kingdom. The participants in the action research studies ranged from 6 to 253. Predominately studies using action research involved nurses in collaboration with patients and family and other health care practitioners to address identified problems in the ICU. Conclusions: Based on this review it appears that action research is a promising methodological approach to address clinical practice improvement in the ICU. Studies retrieved focussed primarily on process and formative evaluation but not on clinical outcomes. There is a need to incorporate outcome assessment in action research in the ICU to increase the framework of action research to improve clinical outcomes. © 2010 Elsevier Ltd.